ANALISIS FAKTOR-FAKTOR PEMBELIAN YANG MEMPENGARUHI REVISI PURCHASE ORDER (PO) MEDIS TERHADAP KEBUTUHAN OBAT DI UNIT FARMASI RUMAH SAKIT GRHA PERMATA IBU DEPOK TAHUN 2024. - Ilahi, Berliani Cinta; Nursanty, Oci Etri; Ningsih, Desy Kartika (SINERGI : Jurnal Riset Ilmiah, 2025)
Logistics management can be described as a management field in charge of managing the logistcs of drugs and medical devices in health services, the medical logistics cycle in hospital has several stages including planning, procurement, receipt, storage, distribution, elimination, and control. All of these activities are interrelated with each other to provide a smooth service in a service to the work unit in need. The process of procuring medical logistics in hospitals involves selecting suppliers and negotiation contracts, a good purchase is a purchase that has established coorperation between buyers and sellers, this is done for the smooth running of a transaction. The purpose of this study was to analyze the purchase of medical logistich for drug needs at the Grha Permata Ibu Depok Hospital Pharmacy Unit. This research is a type of qualitative research field observation and in-depth inetrviews are the collection techniques used with 3 informant samples, assisted by tools such as interview guidelines and checklist sheet. The result of this study indicate that the procoument departement at Grha Permata Ibu Depok Hospital is quite selective in finding suppliers who will become medical logistics suppliers by looking at track records with the payment method used is due 30 to 45 working days and the flow of purchasing document is in accordance with regulation. The conclusion of this study is that Grha Permata Ibu Depok Hospital has not made MOUs with many suppliers and price changes without confirmation from the suppliers are a factor in revising medical purchase order (PO) documents for drug needs in the pharmacy unit.